Pengaruh Motivasi, Pengetahuan Investasi dan Kemajuan Teknologi Terhadap Minat Investasi - I Wayan Adi Wiguna; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2022)
This study was conducted to determine the relationship that exists between motivation, knowledge, and existing technological advances on student investment interest. Hindu University of Indonesia was chosen as the research location where students majoring in accounting in semester 6 and semester 8 were used as research samples with a total of 200 people determined using the slovin formula. The data in this study were obtained from the results of the distribution of questionnaires and were further investigated by the PLS method. From the research process, it was found that the interest of Indonesian Hindu University students, especially accounting majors, to invest was influenced by motivation and knowledge, while technology had no effect on student interest in investing. based on the results of future research, the campus must often hold investment seminars to increase students' knowledge so that they will be motivated to invest.